2011
DOI: 10.1002/cm.20507
|View full text |Cite
|
Sign up to set email alerts
|

Subunit interactions within the Chlamydomonas flagellar spokehead

Abstract: The radial spoke (RS)/central pair (CP) system in cilia and flagella plays an essential role in the regulation of force generation by dynein, the motor protein that drives cilia/flagella movements. Mechanical and mechanochemical interactions between the CP and the distal part of the RS, the spokehead, should be crucial for this control; however, the details of interaction are totally unknown. As an initial step toward an understanding of the RS-CP interaction, we examined the protein-protein interactions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 44 publications
8
42
0
Order By: Relevance
“…The rest of the stalk proteins, including two RIIa domain-containing RSPs, are present in normal amounts. The phenotypes (69), further corroborated by recent cryoelectron tomography of pf24 and the other RS mutants (46) and chemical cross-linking (32), suggest that the two DPY-30 domain-containing RSPs are located in the neck region adjacent to the spokehead, whereas the two RIIa domain-containing proteins are positioned toward the radial spoke stalk base ( Fig. 1D and Table 1).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The rest of the stalk proteins, including two RIIa domain-containing RSPs, are present in normal amounts. The phenotypes (69), further corroborated by recent cryoelectron tomography of pf24 and the other RS mutants (46) and chemical cross-linking (32), suggest that the two DPY-30 domain-containing RSPs are located in the neck region adjacent to the spokehead, whereas the two RIIa domain-containing proteins are positioned toward the radial spoke stalk base ( Fig. 1D and Table 1).…”
supporting
confidence: 65%
“…1) (3, 24, 46) and multiple short helices in the splayed spokehead (50). Additionally, it explains chemical cross-linking of RSP2 and spokehead proteins (32) and at least two proteins involved in the head-stalk connection (70). This subcomplex could further associate with other spoke proteins, such as the dimeric spoke HSP40, which depends on RSP2 for assembly (27).…”
Section: Discussionmentioning
confidence: 98%
“…For example, in the spoke head, RSP4 and 6 are paralogs expressed from duplicated genes (Curry et al 1992), whereas RSP1 and 10 are homologs with membrane occupation and recognition nexus (MORN) repeats. Analysis of recombinant proteins and tagging indicate that each spoke head contains two copies of each protein that is inherently dimeric (Kohno et al 2011;Oda et al 2014b). Furthermore, the RIIa domains in RSP11 and RSP7, and the Dpy-30 domains in RSP2 and RSP23 (NDK5) in the stalk are dimerization and docking (DD) domains of striking similar tertiary structures .…”
Section: Organization Of Rspsmentioning
confidence: 99%
“…It is reported that the CP-RS interactions determine the waveform and the bend direction, whereas RS-IDA interactions influence the velocity of ciliary beating (48). In the alga, C. reinhardtii, the …”
Section: Discussionmentioning
confidence: 99%